2018
DOI: 10.5194/nhess-2017-461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brief communication: Roads and landslides in Nepal: How development affects risk

Abstract: Abstract. The number of deaths from landslides in Nepal has been increasing dramatically due to a complex combination of earthquakes, climate change, and an explosion of road construction. We compare the distribution of landslides in Sindhupalchok district before the 2015 Gorkha Earthquake with those generated by the earthquake to demonstrate that landslides are more than twice as likely to occur near a road than a random distribution. Based on this finding, geoscientists, planners and policymakers must consid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The consequent post-earthquake landslide activities in this region have been reported to have remained active and evolving by recent studies (Kincey et al, 2021;Tian et al, 2020). Due to the combination of heavy rainfall, rugged topography, proximity to the tectonic fault, post-earthquake landslide activity, as well as J o u r n a l P r e -p r o o f ongoing anthropogenic activities like road-building (Mcadoo et al, 2018;Rosser et al, 2021), the study area is susceptible to both natural and anthropogenic landslides.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The consequent post-earthquake landslide activities in this region have been reported to have remained active and evolving by recent studies (Kincey et al, 2021;Tian et al, 2020). Due to the combination of heavy rainfall, rugged topography, proximity to the tectonic fault, post-earthquake landslide activity, as well as J o u r n a l P r e -p r o o f ongoing anthropogenic activities like road-building (Mcadoo et al, 2018;Rosser et al, 2021), the study area is susceptible to both natural and anthropogenic landslides.…”
Section: Study Areamentioning
confidence: 99%
“…The proliferation of informal local roads in Nepal has further increased the risk of rainfall-induced landsliding (Dahal et al, 2010;Devkota et al, 2014;Froude and Petley, 2018;Mcadoo et al, 2018;Petley et al, 2007;Vuillez et al, 2018), and this has been attributed to the non-engineered or informal method of slope excavation for road construction, often crossing terrain with steep angles, without suitable planning, design and drainage and protection measures (Dixit et al, 2021;Hearn and Shakya, 2017;Robson et al, 2021;UNDP, 2011;World Bank, 2012). The study by Mcadoo et al (2018) found that the rainfalltriggered landslides could occur with approximately twice the frequency in areas with poorly constructed J o u r n a l P r e -p r o o f roads than in those without, based on the spatial distribution analysis of landslides and roads in Sindhupalchok district, Nepal. Vuillez et al (2018) also found that within the Phewa watershed in western Nepal, the occurrence of landslides during extreme rainfall events was more prominent in areas intersected by or in close vicinity of the roads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petley et al (2007) observed an upward trend in occurrences of landslides in Nepal since 1978, with Nepal accounting for 10% of all fatal landslides globally (Froude and Petley 2018). In Nepal, landslides are driven by a complex combination of factors, including seasonality, seismic activity, climate change (e.g., heavy rainfall events) and other anthropogenic stressors (e.g., road construction, land conversion) (McAdoo et al 2018;Petley et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Far Western Nepal, where poverty, food insecurity, and social inequity are severe, many of the most productive members of rural households opt to migrate for better economic opportunities (Thieme 2003). Thus, land-use change to connect rural communities with outer markets is considered as one of the drivers of landslides in rural Nepal (Froude and Petley 2018;McAdoo et al 2018;Sudmeier-rieux et al 2019) Until recently, landslide risk had received little attention from Nepal's policymakers due to budgetary restrictions, underreporting of associated losses, siloed institutions with poor interdepartmental collaboration, and competing disaster paradigms that focus largely on disaster response rather than preparedness (Vij et al 2020). Thus, mountain communities and households are typically left to devise their own strategies to mitigate and enhance their resilience to landslide risk.…”
Section: Introductionmentioning
confidence: 99%